Seasonal Prevalence of Mosquitoes Collected from Light Traps in Gyeongsangnam Province, Republic of Korea (2013–2014). Issue 5 (12th July 2018) - Kim, Dong‐Min; Noh, Byung‐Eon; Heo, Jeonghoon; Lee, Wook‐Gyo; Yang, Sung‐Chan; Lee, Dong‐Kyu
Abstract: Adult mosquito surveillance was conducted from 2013 through 2014 at four cattle sheds, a wild bird refuge, and two residential areas located in Gyeongnam Province in the Republic of Korea. Adult mosquitoes were collected in black light traps from April 1, through November 30. Mosquito surveillance was conducted to figure out population densities of vector mosquitoes, possibly invaded mosquitoes and identify various virus infections at the selected sites. A total of 107, 466 females comprising 14 species and 7 genera were collected from 2013 to 2014. The most common species collected were Culex tritaeniorhynchus Giles (63.8%), Anopheles sinensis s.l. (18.9%), Aedes vexans nipponii (Theobald) (7.7%), and Culex pipiens Coquillett (5.1%). Trap indices (TIs) varied widely for species over their range, due to geographical distribution and degree of association with rural and urban communities. The most collected An. sinensis s.l. and Cx. tritaeniorhynchus appeared at a cow shed in Hapcheon (TI 347.5) and a pigsty in Daejeo‐1‐dong, Busan (TI 1, 040.8), respectively, due in part to their situation near breeding sites such as rice paddies. The bi‐weekly population densities for mosquito species were variable for each of the years, apparently as a result of variable annual weather conditions. None of the mosquito species collected tested for the flavivirus including Japanese Encephalitis Virus, West Nile Virus, Dengue Virus, and Zika Virus infections by polymerase chain reaction (PCR) assay were positive.